2021
DOI: 10.1136/bmjopen-2020-044101
|View full text |Cite
|
Sign up to set email alerts
|

Assessing seropositivity for IgG antibodies against SARS-CoV-2 in Ahmedabad city of India: a cross-sectional study

Abstract: ObjectivesTo study the percentage seropositivity for SARS-CoV-2 to understand the pandemic status and predict the future situations in Ahmedabad.Study designCross-sectional study.SettingsField area of Ahmedabad Municipal Corporation.ParticipantsMore than 30 000 individuals irrespective of their age, sex, acute/past COVID-19 infection participated in the serosurvey which covered all the 75 Urban Primary Health Centres (UPHCs) across 48 wards and 7 zones of the city. Study also involved healthcare workers (HCWs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…Ahmedabad Municipal Corporation (AMC), from the state of Gujarat, India, had already completed one large scale population-based sero-surveillance for IgG antibodies against SARS-CoV-2 Virus with an average positivity of 17.61% at the end of June 2020. 7 During the one and half month after the initial survey, there are additional cases of COVID-19. So, a repeat population-based sero-survey was planned to study the COVID-19 seropositivity.…”
Section: Methodsmentioning
confidence: 99%
“…Ahmedabad Municipal Corporation (AMC), from the state of Gujarat, India, had already completed one large scale population-based sero-surveillance for IgG antibodies against SARS-CoV-2 Virus with an average positivity of 17.61% at the end of June 2020. 7 During the one and half month after the initial survey, there are additional cases of COVID-19. So, a repeat population-based sero-survey was planned to study the COVID-19 seropositivity.…”
Section: Methodsmentioning
confidence: 99%
“…V. Murhekar, et al, 2021;Naushin et al, 2021;Padma et al, 2021;Parai et al, 2021;Prakash et al, 2021a. ;Prakash et al, 2021b;Prakash et al, 2021c;Prakash et al, 2021d;Rafi et al, 2021;Ray et al, 2020;Satpati et al, 2020;Selvaraju et al, 2021;Sen et al, 2021;N. Sharma et al, 2020.;Siddiqui et al, 2020;Singhal et al, 2020;Siva Ganesa Karthikeyan et al, 2021;Velumani et al, 2021;Venkataraman et al, 2021) with 831,010 participants in the first wave (COVID-19sero survey-III (July 2021) -Tamil Nadu, 2021.; Misra et al, 2021;Selvaraju et al, personal communication;M.…”
Section: Selection Of Studiesmentioning
confidence: 99%
“…We have documented much higher seroprevalence in Hyderabad (54.2%) than that seen in other states such as Tamil Nadu (31%) [15], Uttar Pradesh, Gujarat, West Bengal, Madhya Pradesh, Karnataka and Chhattisgarh (41%) [16] in the same time frame (November 2020 to January 2021). A few other studies have reported much lower seroprevalence of 17.6% in Ahmedabad [17] and 3.1% in Srinagar [18] in November-December 2020. The findings of our study are similar to those from Mumbai [5], Chennai [6] and in Karnataka [7] conducted during the months of July 2020, suggesting that urban populations have had much higher seroprevalence than the national average prevalent at that time.…”
Section: Discussionmentioning
confidence: 85%